Heralds of global transparency: Remote sensing, nuclear fuel-cycle facilities, and the modularity of imagination. (August 2020) - Lawrence, Christopher
How has commercial remote sensing influenced the framing of public narratives about nuclear programs and weapons of mass destruction? This article examines an early and formative case: In 2002, a Washington-based nongovernmental organization used commercial satellite images to publicly identify the Natanz nuclear facility in Iran. The episode helped inaugurate the 'Iran nuclear crisis' as we have known it since. But it also played a role in fomenting a commercial market for remote sensing, adjusting the role of 'citizen scientist' in the nuclear arms-control community, visualizing a new television journalism beat of 'covering the intelligence community', legitimizing a transforming role of nuclear safeguards inspectors at the International Atomic Energy Agency, and solidifying Iran's nuclear program as 'clandestine'. This article follows the images as they pass through these social worlds and examines how heterogenous actors incorporated remote sensing into their identities and commitments to global transparency.